Intestino médio de larvas de Anticarsia gemmatalis (Hübner) (Lepidoptera: Noctuidae): estudo das células epiteliais ao microscópio de luz e eletrônico - Levy, S. M.; Falleiros, A. M. F.; Gregório, E. A.; Arrebola, N. R.; Toledo, L. A. [UNESP] (FapUNIFESP (SciELO), 2004)
The morphology of the midgut epithelium cells of Anticarsia gemmatalis (Hübner) larvae is described by light and transmission electron microscopy. The midgut of A. gemmatalis is the largest portion of the digestive tract, with three distinct regions: proximal, media and distal. Its wall is formed by pseudostratified columnar epithelial tissue having four cell types: columnar, goblet, regenerative, and endocrine cells. The columnar cells are numerous and long, with the apical portion showing many lengthy microvilli and the basal portion invaginations forming a basal labyrinth. The goblet cells have a large goblet-shaped central cavity delimited by cytoplasmic projections filled with mitochondria. The regenerative cells present electron-dense cytoplasm and few organelles. The endocrine cells are characterized by electron-dense secretory granules, usually concentrated in the cytoplasm basal region.
The larval midgut of anticarsia gemmatalis (hübner) (lepidoptera: Noctuidae): Light and electron microscopy studies of the epithelial cells
Keywords: Lepidoptera; Midgut; Morphology; Ultrastructure; Velvetbean caterpillar; animal; cytology; epithelium cell; intestine; larva; transmission electron microscopy; ultrastructure; Animals; Epithelial Cells; Intestines; Larva; Microscopy, Electron, Transmission